TANGGUNG JAWAB PT INVESTREE RADHIKA JAYA TERHADAP LENDER DALAM PENYELENGGARAAN FINTECH PEER TO PEER LENDING: The Responsibility of PT Investree Radhika Jaya towards Lenders in the Organizing Fintech Peer-to-Peer Lending - Zidane Gideon Fransiskus; Siti Nurbaiti (Faculty of Law, Universitas Trisakti, 2025)
The development of technology in the Industrial Revolution 4.0 era has affected various sectors, including the financial sector with the born of innovation in the form of Financial Technology (Fintech). One form of Fintech that is growing rapidly in Indonesia is Peer to Peer Lending (P2PL), which provides easy access to loans for the community without involving banking institutions. The problem in this study is, how is PT Investree Radhika Jaya's responsibility to lenders in organizing Fintech Peer to Peer Lending. The research method used is normative juridical by analyzing legislation and cases. The results of the study illustrate that PT Investree Radhika Jaya, as the organizer of P2PL, has a responsibility to guarantee the security of lender funds in accordance with applicable regulations, as well as providing a dispute resolution mechanism. Therefore, improvements in risk mitigation and consumer protection are still needed to ensure sustainability and security in the Fintech industry in Indonesia.